The Corona Virus Disease 2019 (Covid-19) Pandemic Appears as a Result of Human Beings not Friendly to the Environment - Elvis Umbu Lolo; Cicik Sudaryantiningsih; Yonathan Suryo Pambudi; Widianto; Richardus Indra Gunawan; Agerippa Yanuranda Krismani (PT FORMOSA CENDEKIA GLOBAL, 2023)
The number of new deadly infectious diseases in the world, including Covid-19, has quadrupled in the last 60 years. For example, HIV is known to have originated from chimpanzees, the Ebola outbreak was related to hunting habits or the use of several species of bats that carried the virus, SARS (Severe Acute Respiratory Syndrome) was transmitted from mongooses to humans, while MERS (Middle East Respiratory Syndrome) was transmitted from humped camels and Bird flu (H5N1), also known as avian influenza, is a viral infection originating from wild birds (chickens) that can attack not only birds, but also humans and other animals. All of the events mentioned above have awakened humanity to exploit natural resources. responsibly so as not to cause the emergence of new diseases such as the corona virus 2019 disease 2019 (covid-2019).